The Using of GIS as Part of ICZM (Integrated Coastal Zone Management) for Environmental Marketing - Baiq Liana Widiyanti (Uniplan: Journal of Urban and Regional Planning, 2020)
Coastal areas are very complex areas, both in terms of the physical environment and socially humanity. This study aims to provide recommendations in theoretical spatial planning in coastal areas based on the ideality level in the concept of sustainable development by using geographic information systems (GIS). This research is a literature study by using data in the form of journals and books that discuss themes related to this. The results of the study are diagrams / schemes which are theoretical conceptual models regarding the handling of problems that occur in coastal areas and how spatial planning in the region should be.